2019
DOI: 10.1111/dgd.12630
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐2 induces extracellular matrix synthesis and TGF‐β2 expression in retinal pigment epithelial cells

Abstract: Macular fibrosis is a vital obstacle of vision acuity improvement of age‐related macular degeneration patients. This study was to investigate the effects of interleukin 2 (IL‐2) on epithelial‐mesenchymal transition (EMT), extracellular matrix (ECM) synthesis and transforming growth factor β2 (TGF‐β2) expression in retinal pigment epithelial (RPE) cells. 10 μg/L IL‐2 was used to induce fibrosis in RPE cells for various times. Western blot was used to detect the EMT marker α‐smooth muscle actin (α‐SMA), ECM mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…IL-1 receptor antagonist (IL-1Ra) treatment that inhibits IL-1β significantly suppressed CNV 56 - 58 . IL-2 participates in RPE cell migration, extracellular matrix (ECM) synthesis, TGF-β2 expression, indicating that IL-2 makes a constructive effect on the fibrosis of macular degeneration 59 . IL-6 is a key mediator for promoting subretinal fibrosis, which is considered as an injured repair in damaged organs 60 , and serum IL-6 level correlates with GA 61 .…”
Section: Cytokinesmentioning
confidence: 99%
“…IL-1 receptor antagonist (IL-1Ra) treatment that inhibits IL-1β significantly suppressed CNV 56 - 58 . IL-2 participates in RPE cell migration, extracellular matrix (ECM) synthesis, TGF-β2 expression, indicating that IL-2 makes a constructive effect on the fibrosis of macular degeneration 59 . IL-6 is a key mediator for promoting subretinal fibrosis, which is considered as an injured repair in damaged organs 60 , and serum IL-6 level correlates with GA 61 .…”
Section: Cytokinesmentioning
confidence: 99%
“…In the context of AMD, RPE cells lose their cell‐cell adhesions and apical‐basal polarity, transforming into mesenchymal cells via EMT 3 . Multiple extracellular ligands, such as galectin‐1 4 and interleukin‐2 (IL‐2), 5 are involved in the initiation and development of the EMT programme in RPE cells 6 . Thoroughly studied for its central role in control of EMT, the ligand transforming growth factor‐beta (TGF‐β) is identified as the master regulator of EMT process 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…TGF-β2 is considered a key component in the development of abnormal fibrosis in the pathological environment. Various studies have confirmed TGF-β2 as a dominant factor in the development of age-related macular degeneration and macular fibrosis or atrophy ( 49 , 50 ). The present results demonstrated that TA not only enhanced cell viability in TGF-β2-treated RPE cells, but also suppressed contractility in collagen gels.…”
Section: Discussionmentioning
confidence: 99%